NOTES ON THE SEMINAR «CURRENT PROBLEMS WITH FORENSIC INVESTIGATION OF GUNSHOT TRACE EVIDENCE AND CIRCUMSTANCES OF FIREARM INCIDENTS», MOSCOW, SEPTEMBER 22–26, 2014 - M. Sonis (Теория и практика судебной экспертизы, 2014)
.